If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -29 = 91 Reorder the terms: -29 + 10x = 91 Solving -29 + 10x = 91 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + 10x = 91 + 29 Combine like terms: -29 + 29 = 0 0 + 10x = 91 + 29 10x = 91 + 29 Combine like terms: 91 + 29 = 120 10x = 120 Divide each side by '10'. x = 12 Simplifying x = 12
| -3-6x=7x+15 | | 9x+5=9x+13 | | 5(m+3)=2m+48 | | 3(5x+4)=18-6 | | 3(15x+4)=18-6 | | 6x^2-6x=12 | | 5x^2-10x+5= | | xa=ba+c | | ln(x-1)=0 | | bx+c=ax | | 7x^3=0 | | =4x-2x+y+6y | | 3x^2+27-30=0 | | 2a-4=132 | | 1x^2-12x+36=0 | | x(x^2)=0 | | x^2+576=10x | | x^2+576=10x^2 | | x+24=10x^2 | | x-x=y | | x-3=y | | 96-5x=7x+54 | | 19x^2+19x+12=0 | | -6w=-8 | | x^2=4x+4+100 | | 4y=256 | | 3y-1=(10y-18)/2 | | (3y-1)/2=(10-18) | | (3y-1)=2(10-18) | | 2(3y-1)=10-18 | | (8x-3)=3(5x+6) | | 3(8x-3)=5x+6 |